The heart and heart conducting system in the kingdom of animals: A comparative approach to its evolution - Solc, David (Experimental and clinical cardiology, 2007)
The phylogeny of the heart and its conducting system is surveyed in the present study, as well as its parallels with ontogeny. A concise review of its evolution in the main taxonomic groups is presented. The aim is to inform physicians on evolutionary connections to the physiology of the human heart conducting system. Furthermore, some unanswered questions in terms of the developmental biology of the heart are offered. It is assumed that some supraventricular arrhythmias are based on remnants of embryonic structures of the pacemaking or conducting tissues; atrial flutter could re-entry through a survived embryonic sinoatrial ring. Some cases of atrial fibrillation could be initiated from remnant embryonic pacemaking cells settled in pulmonary veins.
Keywords: Heart conducting system; Ontogeny; Comparative anatomy; Arrhythmia; Humans; Phylogeny; Heart; Animals